Applicability of Hilf`s Method to the Compaction Control of Soil-rock Mixtures - Brito, A. (2011)
The employment of non traditional materials, such as soil-rock mixtures, in the construction of earthworks, for economical and environmental reasons, poses some new challenges to compaction techniques and their control. Usually, this kind of material results from the bulky rock extraction without explosives, and it can include some large size particles (greater than 0.5 m). Construction control of embankments built with soil-rock mixtures is still a subject that needs investigation, considering that it is necessary to extrapolate current test results, which have been reached by means of the truncation of the grain-size distribution curve, to the actual construction conditions. The behaviour of these materials depends of the relative fractions of theirs constituents, becoming closer to a soil, if the fine fraction is large with the coarser material scattered in it, or closer to a rockfill if the coarser particles are in contact with each other with the fines occupying the spaces between them. One of the control methods widely used in Portugal for embankments is the Hilf’s method, developed for fine soils, since it does not need a previous knowledge of the materials’ characteristics. So, taking into account the materials used in the Odelouca Dam’s shells (weathered schist with a significant fraction of large size particles), constructed in the South of Portugal, this paper presents the results from a laboratory study related to the conditions of application and the applicability of Hilf’s method to coarser soils and soil-rock mixtures. A series of laboratory tests were performed in a large-scale compactor (Toni-tecnik, with a mould diameter of 300 mm). The obtained results of the upstream shell during the construction of Odelouca Dam are presented, seeking his comparison with the Hilf’s method, which avoids the truncation of the material grain-size distribution curve and the subsequent correction of the results. Some conclusions are drawn about the applicability of this method.